AMERICAN SOCIAL CLASS DISSIMILARITY AS REFLECTED IN MICHAEL GRACEY’S MOVIE “THE GREATEST SHOWMAN” - Balqis Majesty Wahana; Mhd Johan (Asosiasi Ide Bahasa Kepri, 2021)
This study aimed investigate about American social class dissimilarity as reflected in Michel Gracey’ movie entitled The Greatest Showman, to reveal the causes in social class dissimilarity in America , to describe the impacts of American Social Class to the main character and the society and to find solution to solve tis social problem as reflected in the film. The objectives of this research were looking the problems that found in Michael Gracey’ film entitled The Greatest Showman. The data were taken from the narration of this movie which are relevant to discussion of the study. The data were collected by watching the movie and reading the movie script in several times, selecting data, discussion from identifying date to report in paper to discribe the condition. The qualitative method used in this research by developing ideas and analyzing the data based on librarian research. The results of this analyzing are people underestimate others and the impact American social class in society of relationship.